Green and efficient synthesis of thioureas, ureas, primary O-thiocarbamates, and carbamates in deep eutectic solvent/catalyst systems using thiourea and urea. (18th June 2021) - Bagherzadeh, Nastaran; Sardarian, Ali Reza; Inaloo, Iman Dindarloo
Abstract : An efficient and general catalysis process was developed for the direct preparation of various primary O -thiocarbamates/carbamates as well as monosubstituted thioureas/ureas by using thiourea/urea as biocompatible thiocarbonyl (carbonyl) sources. Abstract : An efficient and general catalysis process was developed for the direct preparation of various primary O -thiocarbamates/carbamates as well as monosubstituted thioureas/ureas by using thiourea/urea as biocompatible thiocarbonyl (carbonyl) sources. This procedure used choline chloride/tin(ii ) chloride [ChCl][SnCl2 ]2 with a dual role as a green catalyst and reaction medium to afford the desired products in moderate to excellent yields. Moreover, the DES can be easily recovered and reused for seven cycles with no significant loss in its activity. Besides, the method shows very good performance for synthesizing the desired products on a large scale.